A Well-Behaved Maniac: DSc Jan Stenis BSBA MSc Mgmt Sci - Stenis, Jan (Advances in Social Sciences Research Journal, 2025)
The first day of school the whole class beat me up because I was three decimetres taller than the other students and could read for three years. The first day of school was repeated my whole life wherever I went, especially after I was forcibly admitted to Lund for a psychosis. But I was highly sensitive: a HSP with a superior perception of reality. This ability gave me the inspiration to write poems that in 2011 made me a member of the Swedish Writers' Union and in 2018 inducted into the Swedish Haiku Society. In 1997, I invented the Europe model, which in 2005 made me a Doctor of Philosophy at Lund University. I summed up my life-affirming Nordic model in an epic that was published in 2021. The following year, I published my textbook on how the Europe model optimized the resource economy. In 2025, my electronic book on how to preserve the universe came. Thus, the “maniac” always did the right thing but never married because of his very romantic disposition. I compensated for the lack of physical love by worshipping Jesus as the Way, the Truth and the Life in my old age. My motto was Love and Knowledge – in that order! Maybe death would free me from being a Target. Was Mother Maja waiting for me in glorious heaven!? All I wanted was a broad smile and a few kind words from an empathetic lady who could have given me some ordinary tenderness.